Nonlinear 3D projection printing of concave hydrogel microstructures for long-term multicellular spheroid and embryoid body culture1. Issue 11 (7th June 2015) - Hribar, K. C.; Finlay, D.; Ma, X.; Qu, X.; Ondeck, M. G.; Chung, P. H.; Zanella, F.; Engler, A. J.; Sheikh, F.; Vuori, K.; Chen, S. C.
<x xml:space="preserve">Abstract</x> Nonlinear 3D projection printing is developed to generate concave hydrogel microstructures for 3D cell spheroid and embryoid body formation and long-term culture.